The effect of on-site and on-call nurse on exclusive breastfeeding in two different hospital settings: a prospective observational cohort study - Giuseppe Latorre; Domenico Martinelli; Manuela Capozza; Francesca Maria Grosso; Nicola Laforgia; Maria Elisabetta Baldassarre (BMC, 2024)
Abstract Background Exclusive breastfeeding during postpartum hospitalization is very important for ensuring the success of breastfeeding at home. The aim of the study is to determine if the on-site nurse in rooming in improves exclusive breastfeeding ratio. Methods We conducted a prospective observational cohort study to evaluate exclusive breastfeeding during the first three months of life in two Neonatology Units in the South of Italy with different hospital settings: Ente Ecclesiastico Miulli of Acquaviva delle Fonti with on-site nurse h24 (on-site group) and Policlinico of Bari with nurse available on call h24 from Neonatology Unit (on-call group). Results A total of 564 mother-baby dyads were admitted from 3 January to 31 March 2018 (299 in on-site group and 265 in on-call group). In the overall population, exclusive breastfeeding rate was 76.4% at 90-days, confirming the role of nurse and rooming in, independently of modality of setting. Considering the way of delivery, in infants from cesarean section there were higher rates for exclusive breastfeeding at 30 and 90 days of life in on-site group. Conclusions We can assume that the presence of a nurse h24 could better identify breastfeeding problems. Our study suggests the role of on-site nurse during rooming in to encourage exclusive breastfeeding until three months of life in mothers who underwent caesarean section.